HUBUNGAN STATUS GIZI DENGAN JUMLAH CD4+ PADA PENDERITA HIV/AIDS YANG MENJALANI TERAPI ANTIRETROVIRAL: Laporan Kasus Berbasis Bukti - Yunita Ariyanti (2021)
CORRELATION OF NUTRITIONAL STATUS AND CD4+ COUNTS IN HIV/AIDS PATIENTS THAT RECEIVING ANTIRETROVIRAL THERAPY EVIDENCE-BASED CASE REPORT Nutritional status was associated with changes in CD4+ counts in people living with HIV/AIDS that receiving antiretroviral therapy. This study was conducted to find out the correlation of nutritional status based on Body Mass Index (BMI) with CD4+ count in people living with HIV/AIDS that receiving ARV therapy. This research method uses Evidence-Based Case Reports. The strategy of search literature uses BMC, PubMed and EBSCO databases. The assessment of literature quality used the checklist of The Joanna Briggs Intitute (JBI) Critical Appraisal Tools with the criteria inclusion of adults with HIV/AIDS that receiving ARV therapy, male and female, the literature criteria include observational studies such us cross sectional, cohorts, case control, the journals uses Indonesian and English-language from 2016 to 2021. Exclu-sion criteria for pregnant women and children. The results of this study were obtained by two journals, one journal with cross sectional and cohort studies. Statistically, there was no significant association between BMI and CD4+ counts in cross sectional study or cohort. Although there was no significant association, the recovery of CD4+ counts had a higher increase in normal BMI status, overweight and obesity than underweight. Changes in CD4+ counts can indeed be influenced by various factors other than nutritional status, one of which is medical compliance and smoking status.